The complete mitochondrial genome of Petaurista elegans caniceps. Issue 1 (1st January 2016) - Wu, Zhijiu; Hu, Jie; Yang, Zhisong; Yao, Gang; Li, Yanhong; Li, Dayong; Yang, Zaijun
Abstract: The gray-headed flying squirrel Petaurista elegans caniceps is a cryptic mammal which is not well known. Our study sequenced the complete mitochondrial genome of Petaurista elegans caniceps . The mitochondrial genome is 16 520 bp in size, including 22 tRNA genes, 13 protein-coding genes, 12S rRNA, 16S rRNA and 1 control region. Phylogenetic analysis was performed using whole mitogenome sequences with other 14 closely related taxa to assess their phylogenetic relationship. This mitochondrial genome sequence will provide a better understanding for P. elegans caniceps evolution in the future.